Interspecies allometric scaling of antimalarial drugs and potential application to pediatric dosing - Senarathna, Senarathna Mudiyanselage Dona; Batty, Kevin (American Society for Microbiology, 2014)
Pharmacopeial recommendations for administration of antimalarial drugs are the same weight-based (mg/kg of body weight) doses for children and adults. However, linear calculations are known to underestimate pediatric doses; therefore, interspecies allometric scaling data may have a role in predicting doses in children. We investigated the allometric scaling relationships of antimalarial drugs using data from pharmacokinetic studies in mammalian species. Simple allometry (Y = a × Wb) was utilized and compared to maximum life span potential (MLP) correction. All drugs showed a strong correlation with clearance (CL) in healthy controls. Insufficient data from malaria-infected species other than humans were available for allometric scaling. The allometric exponents (b) for CL of artesunate, dihydroartemisinin (from intravenous artesunate), artemether, artemisinin, clindamycin, piperaquine, mefloquine, and quinine were 0.71, 0.85, 0.66, 0.83, 0.62, 0.96, 0.52, and 0.40, respectively. Clearance was significantly lower in malaria infection than in healthy (adult) humans for quinine (0.07 versus 0.17 liter/h/kg; P = 0.0002) and dihydroartemisinin (0.81 versus 1.11 liters/h/kg; P = 0.04; power = 0.6). Interpolation of simple allometry provided better estimates of CL for children than MLP correction, which generally underestimated CL values. Pediatric dose calculations based on simple allometric exponents were 10 to 70% higher than pharmacopeial (mg/kg) recommendations. Interpolation of interspecies allometric scaling could provide better estimates than linear scaling of adult to pediatric doses of antimalarial drugs; however, the use of a fixed exponent for CL was not supported in the present study. The variability in allometric exponents for antimalarial drugs also has implications for scaling of fixed-dose combinations.